Planning Of The Main Distribution Network Of Gerokgak Distribution Reservoir In The Burana Drinking Water Supply System (Spam), Buleleng Regency - Milyandari N.K.N (Jurnal Indonesia Sosial Teknologi, 2023)
The increasing population growth rate in Bali Province has led to the depletion of water sources, while the demand for providing clean drinking water continues to rise each year. To improve water supply, the Central Government, Provincial Government, and Local Authorities are undertaking an effort to construct the Titab Dam with an associated water supply system called the Burana Drinking Water Supply System (SPAM Burana) with a flow rate of 350 liters per second. Considering this situation, a research study is needed to analyze the water demand over the next 15 years based on the projected population using Arithmetic, Geometric, and Least Square Methods in five service areas: Penyabangan Village, Musi Village, Sanggalangit Village, Gerokgak Village, and Patas Village. According to the analysis results, the Geometric Method was used for population projection, with the smallest standard deviation of 185.368 and the coefficient of correlation (r) closest to 1, with a value of 0.877. The water demand for the next 15 years was found to be 82.39 liters per second in the five service areas. To optimize the provision of clean drinking water, the analysis recommends using GIP (Galvanized Iron Pipe) with diameters of 40cm, 20cm, and 25cm, starting from the Gerokgak Reservoir to Patas Village, with a total distribution pipeline length of 15,438 meters. WaterNet, a computer program, is required for simulating water flow in the distribution network with minimal relative errors. The WaterNet analysis results showed that the criteria for flow velocity (0.3 – 1 m/s), headloss (< 10 m/km), and pressure (15 – 100 m for GIP) were all met. The required capacity of the Gerokgak Reservoir for the water supply service is 1400m3.